Non-fusion and growing instrumentation in the correction of congenital spinal deformity associated with split spinal cord malformation: an early follow-up outcome - Hui, Hua (Springer-Verlag, 2013)
STUDY DESIGN: A retrospective case review. INTRODUCTION: To evaluate the safety and efficacy of the non-fusion technique in achieving and maintaining the proper correction for congenital spinal deformity (CSD) and allowing normal spinal growth in patients with split spinal cord malformation (SSCM). MATERIALS AND METHODS: Seven patients who had CSD and SSCM were adopted, with a mean age of 8 years. All the patients in this study received Halo-gravity traction (HGT) prior to expansion of the spine and instrumentation with vertical expandable titanium prosthetic rib, growing rod or their hybrid. Five of them underwent opening wedge thoracoplasty simultaneously. And the two patients with type I SSCM underwent bony spur excision in the initial surgery before corrective manipulation. Then all the patients received a lengthened operation every six months. Changes of their major curve and length of T1–S1 spine were measured, and complications, neurological status were recorded. All the patients were followed up with an average of 32.6 months. RESULTS: Their mean major curve improved from 90.1° to 58.6° with a correction rate of 34.9 %. The T1–S1 length increased from 26.3 to 34.7 cm at final follow-up. Especially, one of the type I SSCM patients whose neurological deterioration was found preoperatively was significantly improved. CONCLUSION: Preoperative Halo-gravity traction followed by non-fusion and growing instrumentation may be effective and safe for young children of CSD associated with SSCM. But it is an ongoing study and additional large multicenter studies are necessary to further assess the safety and efficacy of non-fusion and growing instrumentation.